Fostering of Mathematical Critical Thinking Ability Using ARCS Model and Students’ Motivation - Suherman, Suherman; Zaman, Adib Mustofa; Farida, Farida (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
Mathematical critical thinking skills in mathematics learning is an ability that needs to be mastered by every student in order to support students in the learning process. The purpose of this study was to analyzing the influence and interaction of the ARCS model and learning motivation on students' mathematical critical thinking skills. This research is a quasi-experimental design using cluster random sampling as a sampling technique. The data collection technique used an essay test to determine MCT and a questionnaire to see motivation. The data analysis technique used the normality test, homogeneity, and two-way ANOVA. The results have shown that there is an effect of the ARCS learning model on students' mathematical critical thinking ability, there is no influence of learning motivation on mathematical critical thinking skills, and there is no interaction between ARCS model learning and motivation towards mathematical critical thinking ability. Therefore, the ARCS model can be solution to fostering of mathematical critical thinking abilities.